Injecting International Good Practices into Policy Reforms : The Importance of Study Tours - Eldozdar, Yehia K. (World Bank, Washington, DC, 2012)
In policy reform Advisory Services (AS) projects the concept of 'good practices' often floats around, not knowing when or where to land on a 'project runway.' So the question here is how and when do you inject good practices into regulatory reforms so they yield maximum impact? Whenever terms like 'international expert' and/or 'study tours' are mentioned, projects become vulnerable to criticism of wasted money and shopping sprees. The experience from International Finance Corporation (IFC) AS in the Middle East and North Africa's (AS MENA) 'Alexandria Business Start-up Simplification' Project in Egypt stands out as a good example of a project that used international good practices both at the right time and in the right way.